The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1590/s1516-35982009000500025
|View full text |Cite
|
Sign up to set email alerts
|

In vitro degradation of neutral detergent fiber of high-quality tropical forage according to supplementation with different nitrogenous compounds

Abstract: -The objective of this work was to evaluate the in vitro degradation dynamics of neutral detergent fiber (NDF) of high-quality tropical forage according to supplementation with different nitrogenous compounds sources. A signal grass sample harvested during rainy season was used as basal forage. Casein was used as true protein source and urea:ammonium sulfate (U:AS, 9:1) mixture (urea) as non-protein nitrogen source. The first three supplements were the addition of 0.5, 1.0 and 2.0 mg of casein per mL of final … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 21 publications
3
16
0
8
Order By: Relevance
“…On the other hand, despite the beneficial effects of nitrogen on ruminal fibrolytic activity when low-quality forage is offered to animals , several in vitro studies concluded that supplementation with true protein causes deleterious effects on the degradation of neutral detergent fiber (NDF) from high-quality forage (Paez-Bernal, 2007;Costa et al, 2009;Zorzi et al, 2009), and reductions in gas production from carbohydrates (Cone & Van Gelder, 1999;Mould et al, 2005;Oliveira et al, 2005). However, these negative effects would not be observed upon the addition of urea to the medium (Paez-Bernal, 2007;Zorzi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, despite the beneficial effects of nitrogen on ruminal fibrolytic activity when low-quality forage is offered to animals , several in vitro studies concluded that supplementation with true protein causes deleterious effects on the degradation of neutral detergent fiber (NDF) from high-quality forage (Paez-Bernal, 2007;Costa et al, 2009;Zorzi et al, 2009), and reductions in gas production from carbohydrates (Cone & Van Gelder, 1999;Mould et al, 2005;Oliveira et al, 2005). However, these negative effects would not be observed upon the addition of urea to the medium (Paez-Bernal, 2007;Zorzi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…According to Zorzi, Detmann, Queiroz, Mantovani and Bayão (2009), nitrogen supplementation for cattle reared on pasture during the rainy period increases the efficiency of pasture use by maximizing microbial activity and, consequently, fiber degradation. Protein salt (57% corn meal, 16% soybean meal, 13% urea, 1.3% ammonium sulfate, 1.7% common salt and 11% mineral salt); 2 multiple mixture (44.5% corn meal, 50% soybean meal and 5.5% mineral salt); 3 standard error of the mean; 4 SMin = mineral salt, Supl = supplement, SPro = proteined salt; Smul = multiple mixture); 5 increase in weight gain increase -1 of supplement intake in relation to SMin treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Contudo, em trabalhos conduzidos em ambiente in vitro utilizando forragens tropicais de alta qualidade, similares às observadas em pastagens durante o período das águas, Paez-Bernal (2007), Costa et al (2009) e Zorzi et al (2009 verificaram que a suplementação exclusiva com proteína verdadeira pode causar efeitos deletérios sobre a utilização microbiana da fibra em detergente neutro (FDN), ao passo que a suplementação com ureia permitiria ampliação do crescimento microbiano sobre a FDN (Paez-Bernal, 2007;Zorzi et al, 2009). Entretanto, ponto de equilíbrio entre compostos nitrogenados proteicos e não-proteicos parece definir a máxima utilização dos substratos fibrosos basais (Paez-Bernal, 2007;Zorzi et al, 2009).…”
Section: Introductionunclassified
“…Entretanto, ponto de equilíbrio entre compostos nitrogenados proteicos e não-proteicos parece definir a máxima utilização dos substratos fibrosos basais (Paez-Bernal, 2007;Zorzi et al, 2009).…”
Section: Introductionunclassified
See 1 more Smart Citation